Exploring cross-cultural skills for expatriate managers from Chinese multinationals: Congruence and contextualization - Wang, D.; Fan, David; Freeman, S. (Springer New York LLC, 2017)
This study explores what cross-cultural skills are essential for Chinese expatriate managers working in varied host countries, and how home and host contextual factors play a role in constraining the effective application of cross-cultural skills. To build a robust theoretical framework for expatriates’ cross-cultural skills, we integrate social learning theory with a contextual perspective that extends current knowledge of the cross-cultural skill framework. We conducted in-depth interviews with Chinese expatriate managers, foreign colleagues of expatriates, and expatriate supervisors to develop a holistic view on this topic. The findings demonstrate that Chinese expatriate managers working in the Middle East or Africa highly require self-maintenance skills to buffer negative influence of tough local work conditions, while interpersonal and communication skills are more important for those working in Europe or Australia to comprehend culturally different social expectations. Furthermore, Chinese expatriate managers’ home-development interpersonal and communication skills are not readily transferable to foreign contexts, mainly due to host perceptions that value work-life balance and a more equal relationship between leader and subordinates compared to the Chinese working values. This study extends expatriate skill literature by incorporating contextual factors to elaborate contextual influence on skills, and the findings have theoretical and practical significance for expatriate management from emerging market multinationals.